Isolation and Characterization of a Bismuth(II) Radical. Issue 36 (27th July 2015) - Schwamm, Ryan J.; Harmer, Jeffrey R.; Lein, Matthias; Fitchett, Christopher M.; Granville, Simon; Coles, Martyn P.
Abstract More than 80 years after Paneth's report of dimethyl bismuth, the first monomeric BiII radical that is stable in the solid state has been isolated and characterized. Reduction of the diamidobismuth(III) chloride Bi(NONAr)Cl (NONAr=[O(SiMe2NAr)2]2−; Ar=2, 6‐iPr2C6H3) with magnesium affords the BiII radical .Bi(NONAr). X‐ray crystallographic measurements are consistent with a two‐coordinate bismuth in the +2 oxidation state with no short intermolecular contacts, and solid‐state SQUID magnetic measurements indicate a paramagnetic compound with a single unpaired electron. EPR and density functional calculations show a metal‐centered radical with >90 % spin density in a p‐type orbital on bismuth.